Acute Colonic Pseudo-Obstruction (Ogilvieʼs Syndrome) after Hip Arthroplasty - Ziroglu, Nezih; Oruç, Sevinç Ödül (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Ogilvieʼs syndrome is a clinical entity that occurs with signs of excessive dilatation of the colon and obstruction, despite the absence of a mechanical obstruction. Although its etiology remains uncertain, anticholinergic drugs, metabolic disorders, diabetes mellitus, hyperparathyroidism, Parkinsonʼs disease, major orthopedic interventions, or blunt abdominal trauma are considered to be possible causes. Imbalance in sympathetic innervation plays a role in the pathogenesis. The characteristic feature of the syndrome is the presence of a major trauma or surgical history. Although this is an uncommon complication, especially after hip and knee arthroplasty, it is an important cause of mortality and morbidity. Conservative or surgical colonic decompression and anticholinergic agents play a role in the treatment of Ogilvieʼs syndrome, which is defined as acute colonic pseudo-obstruction (ACPO). In this case report, we present the postoperative process of an elderly patient with comorbid diseases who underwent hemiarthroplasty due to a hip fracture as a result of a domestic fall. We will discuss the diagnosis of ACPO and the approach to multidisciplinary management of the treatment in a case that is frequently encountered in daily practice and starts as a normal report. We aim to remind surgeons that they may encounter ACPO in the postoperative period and to emphasize that mortality and morbidity can be reduced with early diagnosis and a multidisciplinary approach. We would like to emphasize that Ogilvieʼs syndrome should be included in the differential diagnosis portfolio of all orthopedic surgeons.
Keywords: Ogilvieʼs syndrome; acute colonic pseudo-obstruction; hemiarthroplasty complications; acute abdomen; hip fracture